In Vivo Contactless Brain Nanothermometry. (31st October 2018) - del Rosal, Blanca; Ruiz, Diego; Chaves‐Coira, Irene; Juárez, Beatriz H.; Monge, Luis; Hong, Guosong; Fernández, Nuria; Jaque, Daniel
Abstract: Despite attracting increased attention from clinicians, brain temperature distribution, fluctuations, and changes in response to external stimuli are still largely unknown and refractory to conventional temperature‐probing approaches. Fluorescence nanothermometry in the second near‐infrared window (NIR‐II, 1000–1700 nm), as shown here, can provide contactless brain thermal sensing through the scalp and skull in real time with a subdegree resolution. As a proof of concept, Ag2 S nanothermometers have been used to monitor brain thermoregulation in a cooling/heating process and temperature changes associated to a barbiturate coma. Abstract : The thermal sensitivity of infrared‐emitting Ag2 S nanodots enables in vivo, real‐time contactless brain thermometry. The lack of techniques for continuous, minimally invasive probing of brain temperature has complicated its study despite its relevance in brain physiology and pathology. Luminescence nanothermometry overcomes this limitation, as demonstrated here by live tracking of drug‐induced brain temperature changes and their link to neural activity.